Goal adjustment processes as coping responses to a blocked goal: the sample case of ostracism - Rühs, Farina; Greve, Werner; Kappes, Cathleen (Frontiers in Psychology, 2025)
IntroductionRecently, Rühs et al. (2022) used an adapted ostracism-paradigm to study goal adjustment processes, and goal disengagement processes (GD) in particular, as regulatory responses to goal-blocking situations such as ostracism. The present study conceptually replicates this study and extends it by inclusion of sub-personal indicators of GD in the paradigm.MethodsThe goal to belong to a newly formed group was induced in 188 participants (Induction Phase). Afterwards, blockage of this goal was experimentally manipulated via ostracism: Participants were either included or excluded from their group in a virtual ball game (Cyberball, Blockage Phase). Finally, participants worked alone on a cognitive task to give regulatory responses some time to unfold. After each phase, dependent measures were recorded (e.g., indicators of GD and well-being).ResultsExclusion (vs. inclusion) in Cyberball lead to a decrease in subjective attainability of the belonging goal (goal blockage) and to affective-cognitive and behavioral GD (e.g., explicit devaluation of the belonging goal and the own group, behavioral deprioritization of ostracizing compared to new group members in a following game). However, ostracism had no effect on implicit group evaluation (repeated IATs showed a constant own group bias) and although excluded participants recovered from ostracism-induced impairments in emotions and needs, associations between recovery and GD indicators were mixed.DiscussionMost of the results of Rühs et al. (2022) could be replicated. Beyond that, the present study showed divergence of personal and sub-personal indicators of cognitive-affective GD (i.e., change in explicit and implicit group evaluations). This illustrates the importance of combining personal and sub-personal perspectives in GD research. Taken together, the study contributes to a conceptual and functional clarification of GD processes and, at the same time, offers a fruitful new perspective on coping with ostracism.